Engineering turbulence modelling and experiments 5 : proceedings of the 5th International Symposium on Engineering Turbulence Modelling and Experiments, Mallorca, Spain, 16-18 September 2001 /: proceedings of the 5th International Symposium on Engineering Turbulence Modelling and Experiments, Mallorca, Spain, 16-18 September 2001. (2002) - Unknown
No abstract available